PARADIGMA TAFSIR AL-MANAR - Saifullah Saifullah (IAIN Ponorogo, 2016)
Abstract: The essential of Al-Mana>r in the process of interpretation become its interpretation phenomenal. Many names were given indistinguishing al-Mana>r style such al-manhaj al-ijtima>y, al-laun al-adaby al-ijtima>’y and so forth. The writer elaborates the paradigm that used by al-mana>r’s author to investigate the reasons in giving various naming. As the result, those naming are understandable. This article investigated al-Mana>r paradigm into three perspectives. First, interpretation means an earnest effort which implemented to decide some cases which are not discussed in Qur’an and hadist. In consequence, human taught becomes an important aspect in interpreting. Second, all the effort is an attempt to make the interpretation of Qur’an as guidance (hida>yah). Then third, interpretation effort is an attempt to make Qur'an readers happiness in this world and in the hereafter. Al-Mana>r has inspired various interpreting works. Therefore, Al-Mana>r refers to the social interpreting (al-madrasah al-'aqliyah al-ijtima>'iyyah). Al-Mana>r paradigm can be categorized as rational paradigm because it puts sense in the important position. Muhammad 'Abduh argues that,